Profile of PBL Model Assisted by Digital Books to Improve Problem Solving Ability of High School Students on Dynamic Fluids - Nova Allysa Qotrunnada; Binar Kurnia Prahani (Jurnal Penelitian Pendidikan IPA, 2022)
This research was conducted with the aim of analyzing the problem-solving ability profile of high school students as a consideration in applying the Problem Based Learning (PBL) model based on digital books on Dynamic Fluids. The survey method used is a preliminary survey method. Data collection techniques for written exams, questionnaires, and interviews with teachers and students. This research was conducted in Gresik district with a total of 143 high school students from 5 classes in class XI, there were 78 boys and 67 girls. This study was conducted in the even semester of 2020/2021. Written test data were analyzed descriptively qualitatively. From the results of research based on problem-solving abilities that were tested on 143 students in the low category with a range of 0-40 as many as 133 students consisting of 76 men and 58 women. Medium category with a range of 41 – 70 as many as 9 students consisting of 0 boys and 9 students. While the High category with a range of 71 - 100 as many as 1 student, namely 1 female. Applying PBL techniques will improve students' problem-solving skills. Therefore, it can be concluded that in order to improve students' problem-solving skills, they need updates in learning, such as the application of an attractively packaged PBL learning model that is adapted to the current learning era